COMPLICATIONS OF EPIDEMIC PAROTITIS IN EARLY CHILDHOOD: CLINICAL AND EPIDEMIOLOGICAL PERSPECTIVES - Masharipova , Shakhista (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
Epidemic parotitis remains a relevant issue in pediatrics and public health despite the widespread implementation of vaccination. In young children, the disease is characterized by a variety of clinical manifestations and a risk of complications affecting multiple organs and systems. Particular importance is associated with involvement of the central nervous system, pancreas, and other organs, which may determine the severity of the disease. The study of clinical and epidemiological features of complications of epidemic parotitis in early childhood is essential for timely diagnosis, prevention of adverse outcomes, and improvement of preventive strategies.